From quality gurus and TQM to ISO 9001:2015: a review of several quality paths - Fonseca, Luís (2015)
A revision of several paths for the Quality journey is presented: from Quality Gurus and Total Quality Management (TQM) models to the ISO 9000 International Standards Series. Since ISO 9001:2008 is now in the revision process to the expected ISO 9001:2015 version, an analysis is made of he proposed changes and the underlying reasons and the impacts foreseen on the more than 1.3 Million certified organizations. This revision should be a step towards TQM and reflect the changes of an increasingly complex, demanding and dynamic environment, while assuring that complying organizations are able to provide conformity products and services that satisfy their customers. Major benefits are expected such as less emphasis on documentation and new/reinforced approaches: consideration of Organizational Context and (relevant) Stakeholders, Risk Based thinking and Knowledge Management.